Inovasi Dalam Pemberdayaan Ekonomi Pesantren Melalui Program Inkubasi Bisnis: Studi Kasus Usaha Perikanan Bumpes Ulul Albab Yogyakarta - Syahrudin, Syahrudin; Isa, Khairunesa; Susanto, Roni (Bale Pengabdian: Journal Of Community Service (BPJCS), 2025)
This study analyzes the economic transformation of an Islamic boarding school through a Business Incubation Program in the fisheries unit of BUMPes Ulul Albab Yogyakarta. Using a qualitative case study, data were collected through in-depth interviews, participant observation, and document analysis, and analyzed with the Miles and Huberman interactive model. Findings show that before the program, the fisheries business faced structural challenges, including high feed costs, dependence on external seed, weak management, lack of financial records, and low entrepreneurial literacy among students. After implementation, significant changes appeared in three aspects: first, technical diversification of commodities such as catfish, gourami, and pangasius, along with feed innovation using local resources like azolla, papaya leaves, banana stems, and fermented pellets; second, institutional strengthening through a student cooperative with transparent finance and profit reinvestment; third, socio-cultural change marked by a spiritualpreneur ethos integrating spiritual values, economic independence, and social responsibility. The study concludes that the model improves economic performance while fostering a sustainable Islamic economic ecosystem with replication potential. It also highlights the importance of local adaptation, institutional support, and cross-sector collaboration for scalability future.